The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2265.2007.02989.x
|View full text |Cite
|
Sign up to set email alerts
|

High risk of pituitary dysfunction due to aneurysmal subarachnoid haemorrhage: a prospective investigation of anterior pituitary function in the acute phase and 12 months after the event

Abstract: GH deficiency (GHD) was the most common pituitary deficit at 12 months after SAH and the majority of the patients (87.5%) had isolated GHD. During the 12-month follow-up, pituitary function was found to either improve or worsen in a considerable number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 28 publications
8
85
3
3
Order By: Relevance
“…This pattern has also been described after traumatic brain injury and has been argued to be a part of a more general response to severe acute illness. [2] Similar findings following SAH with high incidences in the acute stage that later resolves has also been demonstrated by Tanriverdi et al [31] and Klose et al [24] In most cases, pituitary impairments were either new or had resolved at followup compared to the acute stage. Similar findings have also been noted in longitudinal studies by Aimaretti et al, [3] Tanriverdi et al [31] and Karaca et al [23] As stated above, acute phase abnormalities that later resolves may be a transient functional response, but may also represent the restorative capacity of the hypothalamic structures involved.…”
Section: Hormonal Abnormalities After Sah By Axissupporting
confidence: 68%
See 1 more Smart Citation
“…This pattern has also been described after traumatic brain injury and has been argued to be a part of a more general response to severe acute illness. [2] Similar findings following SAH with high incidences in the acute stage that later resolves has also been demonstrated by Tanriverdi et al [31] and Klose et al [24] In most cases, pituitary impairments were either new or had resolved at followup compared to the acute stage. Similar findings have also been noted in longitudinal studies by Aimaretti et al, [3] Tanriverdi et al [31] and Karaca et al [23] As stated above, acute phase abnormalities that later resolves may be a transient functional response, but may also represent the restorative capacity of the hypothalamic structures involved.…”
Section: Hormonal Abnormalities After Sah By Axissupporting
confidence: 68%
“…This prevalence of endocrine disturbances is consistent with previous studies by Dimoupolou et al, [10] Kreitschmann-Andermahr et al, [25] Aimaretti et al [3] and Tanriverdi et al [31] (37.5-68.2% prevalence at follow-up), but contrasts to results from Klose et al [24] and Lammert et al [26] who found few or no abnormalities at confirmatory testing. Gardner et al [16] recently reported 12% hypopituitarism in their patient series, however also with nonaneurysmal SAH patients included.…”
Section: Discussioncontrasting
confidence: 53%
“…In the current study, comparable results were obtained regarding the cognition of patients with aSAH, with 52/135 subjects exhibiting cognitive dysfunction (38.52%). Previous studies have demonstrated that patients with aSAH exhibit pituitary hormone deficiencies in the acute and chronic stages, including deficits in gonadotrophin, somatotropin and T4 (18)(19)(20)(21)(22). In the present study, 31 subjects exhibited hypothyroidism, with elevated levels of TSH and normal levels of FT3, FT4, TT3 and TT4 in the chronic stage.…”
Section: Discussionmentioning
confidence: 51%
“…A number of studies, often incorporating patients with both SAH and traumatic brain injury (TBI), have concluded that hypopituitarism is common in this patient group (1,2,3,4,5), with a systematic review by Schneider et al in 2007 (6) concluding that hypopituitarism is present in 47% of patients in the chronic phase after SAH. In contrast, Klose et al (7), evaluating 61 patients prospectively, concluded that SAH was uncommon having failed to identify a single case.…”
Section: Introductionmentioning
confidence: 99%